Stała interpretacyjna: status rzeczy w poezji Wallace’a Stevensa - Bartczak, Kacper (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
Stevens’s poems grant a curious status to material reality. Famously abstract, they refuse to abandon the realm of the material. Rather, “material reality” is inseparable from “abstract” concepts. Stevens’s position is pragmatist: the status and significance of material objects is founded by the entirely human linguistic/mental activity, which is also an interpretive activity. The poem is a site of initiating this activity. As such, Stevens’s poetics remains in opposition to other aesthetic positions: the linguistic idealism of Mallarmé, the metaphysical realism of Miłosz and Herbert, and the material realism of Ponge and American “objectivists”. While the metaphysical positions tend to overcome the material, the realistic poets will reify it by “taking the side of things”. Stevens’s poetic pragmatism sees no lure in the extra-material, while also refusing to see matter as meaningful in itself, beyond the human interpretive activity.